Value For Money (VFM) assessment framework for Public Private Partnership (PPP) approach / Kharizam Ismail - Ismail, Kharizam (2012)
In a generic sense, when procuring Public Private Partnership (PPP) projects, value for money (VFM) assessment could be determined through a comparative analysis of contractors' proposals against VFM documentation. Principally, value for money is a broad term that captures both elements of financial and non-financial elements in the evaluation of VFM. Several diverse approaches to assess value for money (VFM) exist and are used in different countries. Value for money assessment methods have been criticised on numerous grounds with respects to: accuracy of risk transfer; discount rate methodology; limitation scope-'of non-financial and consideration of long term evaluation. Hence, the aim of this study is to develop a complete VFM assessment framework for PPP projects embracing financial and non-financial elements across project phases (i.e., strategy formulation; procurement; construction and operation phase) based on four (4) objectives: to identify the essential factors for PPP implementation; to determine the VFM drivers in PPP projects; to investigate the elements of Public Sector Comparator (PSC) as a VFM assessment framework; and finally to develop a VFM assessment framework for PPP projects. Two methods of empirical research using questionnaire survey and case studies (semi-structured interviews) were conducted with PPP stakeholders. In order to underpin the questionnaire survey, three case studies were conducted using structured interviews with government agencies; consultants and contractors. The VFM assessment framework was validated using semi structured interview approach. The results establish the significant financial and non- financial elements fundamentals in the development of PSC at each stage of PPP life cycle. The results identify five most important financial elements at all the phases of PPP approach. Twelve (12) non-financial elements have been identified for the strategy formulation phase; ten (10) at the procurement phase; eleven (11) for the construction phase and twelve (12) non-financial elements to be integrated in the operation phase. The research outputs seek to facilitate a comprehensive dimension of VFM assessment method for PPP projects in Malaysia and provide significant impacts to the government, consultants and contractors as PPP stakeholders.